English Indonesia-Chan: OPUS-MT Powered Chatbot - Lasama, Jerry; Sudianto, Sudianto; Ramadhani, Rafian; Hilmawan, Muhammad David; Aldean, Muhammad Yusril; Satria, Muhammad Adhan Hady (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2024)
The COVID-19 pandemic has shown an increasing trend of digital platform users on social media such as Whatsapp, Facebook, Instagram, and Discord. The social media that is widely used to communicate massively is Discord. Discord already has 250 million registered active users from various countries worldwide. However, users from various countries create language differences when communicating. So we need a method for translating foreign languages, especially English to Indonesian, easily and quickly to make communication more understandable. This study aims to create a Discord chatbot that translates English sentences into Indonesian. The method built in the chatbot is designed using the MarianNMT model for language translation and the English corpus dataset from Open Parallel corPUS (OPUS). The model was trained using 15 epochs and obtained evaluation results with a loss of 0.0047.